Electromagnetic Field Exposure in Kindergarten Children: Responsive Health Risk Concern - Acharya, Shiva Raj; Shin, Yong Chul; Moon, Deog Hwan; Pahari, Sandip (Frontiers in Pediatrics, 2021)
Long-term exposure to physical agents can be detrimental to children due to their vulnerability. This study aimed to assess and compare the EMF exposure level around the kindergartens from the underground transmission line (UGTL). We investigated randomly selected 24 kindergartens based on the location of the underground transmission line. The EMF emission levels were measured using an EMDEX II (Electric and Magnetic Digital Exposure Meter). The maximum mean value of the EMF emission level was 13.5 mG around the kindergartens and 17.7 mG from the point of UGTL to kindergartens. EMF emission level around the kindergartens was significantly associated with the location of the UGTL (t=-7.35, P<0.001). These estimates aren’t trivial as long-term exposure to EMF among kindergarten children can lead to different health problems. Routine monitoring of EMF emission levels is recommended including the awareness of EMF exposure to public citizens